Perpustakaan Anak Di Pekanbaru Dengan Pendekatan Arsitektur Futuristik - Nur Adela Sobri Rezki; Pedia Aldy; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Children library has a very important role for children and families. It’s a place for children to get to know the various learning resources and foster the fun of books. It’s also an interacting place for children and families. The development of information technology today can not be separated with modern human life. Similarly in the children library. Therefore, the children library should follow the development of technology and information in support of its programs and services. Thechildren library in Pekanbaru now has not been able to answer the needs of information technology literacy because it does not have the right system and infrastructure. In an effort to anticipate thedevelopment of the era to the next era, the children library should be oriented to the future. Children libraries in the future, in addition to reading and learning, also become a social and creative node to collaborate and create content. Therefore, the concept of library must also support those needs. The design of children library using futuristic approach, which is future-oriented and adaptive to the times. It’s realized by combining the introduction of media and futuristic technology to children with creative and innovative collaboration. Design strategy in this research include functional analysis and environmental condition analysis. Based on the function and theme of building design, emerged a concept of